Spatial organization of the Pampas fox in a grassland relict of central Argentina: A flexible system - Luengos Vidal, Estela Maris (2012)
The Pampas fox (Pseudalopex gymnocercus) is a generalist South American canid that adapts well to the human-dominated landscape of the Argentine pampas, which is largely converted to agriculture and pastures. However, little is known about its ranging behaviour and spatial organization in relict native grasslands. We captured and tracked 13 radio-tagged adult foxes between December 1998 and June 2005 in Ernesto Tornquist Provincial Park, a protected area with a dense population of wild horses, an important food item for foxes. The home range of 10 adult males averaged 1.40 ± 0.96km 2 (mean ± sd; 95% minimum convex polygon, MCP) and was not significantly larger than that of three adult females, 1.20 ± 1.07km 2 (95% MCP). Evidence of individual's site fidelity over the study period is indicative of locally abundant food resources all year round. It is likely that the availability of horse carcasses is a main driver of the spatial organization of Pampas foxes in this population. Our population density estimate of 1.1-1.5 foxes per km 2 falls within the know range of population densities for Pampas foxes, and was close to the upper limit, as also expected from an abundant and aggregated food resource such as horse carrion. Reduced hunting pressures, however, may also contribute to explain the relatively high population densities of foxes in this protected area.